Laminate having semiconductor carbon nanotube

A laminate with a conductive substrate and dispersed semiconductor CNTs using a hydrophobic dispersant improves electrode responsiveness by suppressing aggregates and metallic CNTs, ensuring clear optical transitions for effective electrochemical detection.

JP2025002129APending Publication Date: 2025-01-09NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023102073
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

The presence of CNT aggregates and metallic CNTs in laminates using glassy carbon substrates impedes the electrode response for detecting substances, and achieving surface flatness is difficult, hindering the effectiveness of semiconductor CNTs in electrochemical detection.

Method used

A laminate is developed with a conductive substrate and a semiconductor carbon nanotube-containing layer, using a hydrophobic dispersant to isolate and disperse semiconductor CNTs, with specific optical absorption peaks in the near-infrared region, achieved through a centrifugation process and spiral airflow evaporation to form a uniform layer.

Benefits of technology

The laminate suppresses CNT aggregates and metallic CNTs, enhancing electrode responsiveness to detected substances, particularly biomolecules, by ensuring a dispersed and flat semiconductor CNT layer with clear optical transitions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002129000001_ABST
    Figure 2025002129000001_ABST
Patent Text Reader

Abstract

To provide a laminate having a semiconductor CNT isolated and dispersed on a substrate while suppressing the presence of CNT aggregates or the intermingling of metallic CNT.SOLUTION: A laminate comprises a conductive substrate and a semiconductor CNT-containing layer. The semiconductor CNT-containing layer is provided on the conductive substrate. The semiconductor CNT-containing layer includes a semiconductor CNT and a hydrophobic dispersant that allows distinguishing the tube structure of the semiconductor CNT. The semiconductor CNT-containing layer has an absorbance of 0.01 or more and has one or more optical absorption peaks in a near-infrared wavelength region in which LWInt80% is 35 meV or less and LWInt50% is 70 meV or less.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a laminate that can be used for modified electrodes and the like that detect target substances such as biomolecules by electrochemical techniques. [Background technology]

[0002] Semiconductor carbon nanotubes (hereinafter, "carbon nanotubes" may be referred to as "CNTs"), whose energy levels of the conduction band and valence band change depending on the tube structure, can be used as a modification material for electrodes that detect target substances such as biomolecules by electrochemical techniques. Glassy carbon is generally used as an electrode substrate for CNT-modified electrodes for detecting biomolecules (e.g., Non-Patent Document 1).

[0003] However, the laminate obtained by coating the glassy carbon with the CNT dispersion liquid directly hinders the electrode response of the target substance by the semiconducting CNT due to the presence of CNT aggregates or metallic CNTs. In addition, it is difficult to achieve a flat surface for the laminate obtained by modifying the surface of a general glassy carbon with CNTs. The low flatness of the laminate surface is also a cause of hindering the electrode response of the target substance by the semiconducting CNT. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6752432 [Non-patent literature]

[0005] [Non-Patent Document 1] V. Goornavar et al., Mater. Sci. Eng. C 40 (2014) 299-307 [Non-Patent Document 2] M. Takemoto et al., Analytical Sciences 36 (2020) 441-446 [Non-Patent Document 3] Y. Hirana et al., Scientific Reports 3 (2013) 2959 Summary of the Invention [Problem to be solved by the invention]

[0006] The present application has been made in view of the above circumstances, and has an objective of providing a laminate that suppresses the presence of CNT aggregates or metallic CNTs and includes semiconducting CNTs that are isolated and dispersed on a substrate. [Means for solving the problem]

[0007] The laminate of the present application has a conductive substrate and a semiconducting carbon nanotube-containing layer provided on the conductive substrate and containing semiconducting carbon nanotubes and a hydrophobic dispersant capable of identifying the tube structure of the semiconducting carbon nanotubes, and the semiconducting carbon nanotube-containing layer has an absorbance of 0.01 or more and an LW Int80% is 35 meV or less and LW Int50% The modified electrode of the present application is a modified electrode for detecting a substance to be detected by an electrochemical method, and includes the laminate of the present application.

[0008] The method for producing the laminate of the present application includes a centrifugation process in which a dispersion liquid containing semiconducting carbon nanotubes, a hydrophobic dispersant capable of identifying the tube structure of the semiconducting carbon nanotubes, and a dispersion medium is centrifuged at a centrifugal force of 7,000 x g to 20,000 x g for at least one hour to obtain a supernatant liquid, and a coating process in which the supernatant liquid is placed on a conductive substrate, the dispersion medium is evaporated, and a semiconducting carbon nanotube-containing layer containing the semiconducting carbon nanotubes and the hydrophobic dispersant is formed on the conductive substrate. Effect of the Invention

[0009] In the laminate of the present application, the semiconductor CNT-containing layer has a predetermined light absorption peak in the near-infrared wavelength region. That is, the semiconductor CNT-containing layer of the laminate of the present application is suppressed in the presence of CNT aggregates and the presence of metallic CNTs. Therefore, the laminate of the present application can be used for a modified electrode having excellent electrode response to a substance to be detected. The modified electrode of the present application includes the laminate of the present application. Therefore, the modified electrode of the present application can obtain a modified electrode having excellent electrode response to a substance to be detected. In the manufacturing method of the laminate of the present application, a predetermined centrifugation process is performed on a dispersion liquid containing a semiconductor CNT, a hydrophobic dispersant that disperses the semiconductor CNT, and a dispersion medium. Therefore, the manufacturing method of the laminate of the present application can obtain a laminate in which the presence of CNT aggregates and the presence of metallic CNTs are suppressed. [Brief description of the drawings]

[0010] [Figure 1] 1 shows the optical absorption spectrum of the mixed liquid of Example 1 (-) and the optical absorption spectrum of the semiconducting SWCNT dispersion of Example 1 (◯). [Diagram 2] 2D PL map of the semiconducting SWCNT dispersion of Example 1. [Diagram 3] 1 shows the optical absorption spectrum of the semiconducting SWCNT composite of Example 1A. [Figure 4] 1 shows the optical absorption spectrum of the semiconducting SWCNT composite of Example 1B. [Diagram 5] FIG. 1C is a top view schematic diagram of the semiconducting SWCNT composite of Example 1C. [Figure 6] CV curve of Ru(NH3)6 2+ / 3+ in Example 1. [Figure 7] CV curve of Fe(CN)6 3- / 4- in Example 1. [Figure 8] CV curve of 3HK in Example 1. [Figure 9] 1 shows an optical absorption spectrum of a SWCNT dispersion liquid of a comparative example. [Figure 10] 1 shows an optical absorption spectrum of a comparative SWCNT composite. [Figure 11] CV curve of Ru(NH3)6 2+ / 3+ as a comparative example. [Figure 12]CV curve of comparative example Fe(CN)6 3- / 4-. [Figure 13] CV curve of 3HK for comparison. [Figure 14] 1 shows the optical absorption spectrum of the semiconducting SWCNT dispersion of Example 2. [Figure 15] 2D PL map of the semiconducting SWCNT dispersion of Example 2. [Figure 16] 2 shows the optical absorption spectrum of the semiconducting SWCNT composite of Example 2A. [Figure 17] Optical absorption spectrum of the semiconducting SWCNT composite of Example 2B. [Figure 18] CV curve of Ru(NH3)6 2+ / 3+ in Example 2. [Figure 19] CV curve of Fe(CN)6 3- / 4- in Example 2. [Figure 20] CV curve of 3HK in Example 2. [Figure 21] FIG. 1 is a schematic cross-sectional view of an apparatus for forming a semiconducting CNT-containing layer using a spiral airflow. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the laminate, modified electrode, and laminate manufacturing method of the present application will be described based on the embodiment and examples. In the present application, when "-" is used to express a range between two numerical values, these two numerical values ​​are also included in this range. Note that duplicated explanations will be omitted as appropriate. The laminate of the embodiment of the present application includes a conductive substrate and a semiconductor CNT-containing layer. The conductive substrate is a substrate having an electrical conductivity of 0.5 S / cm-5000 S / cm. The electrical conductivity of the conductive substrate is preferably 20 S / cm-200 S / cm.

[0012] Surface roughness R of conductive substrate a is preferably 2.0 nm or less, and more preferably 1.0 nm or less. This is because the flatness of the conductive substrate surface is reflected in the flatness of the laminate surface, and the electrode response of the detected substance on the laminate surface is improved. ais calculated based on the measurement results of the surface unevenness using a surface roughness measuring device in accordance with the Japanese Industrial Standards (JIS). An example of the conductive substrate is a carbon substrate. The carbon substrate may be made of carbon, or may be a substrate other than carbon, in which a carbon film is provided on at least a part of the surface, for example, on at least one surface on which the semiconductor CNT-containing layer is provided or on the entire surface.

[0013] The semiconductor CNT-containing layer is provided on a conductive substrate. The semiconductor CNT-containing layer contains a semiconductor CNT and a hydrophobic dispersant capable of identifying the tube structure of the semiconductor CNT. The tube diameter of the semiconductor CNT is preferably 0.6 nm to 1.7 nm, but is not particularly limited. In addition, there is no particular limit to the method of synthesizing the semiconductor CNT. From the viewpoint of practicality, the semiconductor CNT is preferably a semiconductor SWCNT.

[0014] A dispersant that can identify the tube structure of semiconducting CNTs is one that, when mixed with a CNT mixture containing multiple types of CNTs, selectively disperses semiconducting CNTs in the dispersion medium. When the tube structure of CNTs is expressed using the tube structure index (n, m) described below, called the chiral index, if the remainder when 2n+m is divided by 3 is 1 or 2, it is a semiconducting CNT, and if the remainder is anything other than that, it is a metallic CNT. The metallic CNTs are not dispersed in an isolated state in the dispersion medium by this dispersant, but aggregate in the dispersion. Therefore, if a dispersion containing multiple types of CNTs and this dispersant is separated into a supernatant and a precipitate by centrifugation or the like, the semiconducting CNTs can be recovered from the supernatant.

[0015] The hydrophobic dispersant refers to a dispersant having a solubility in water at 25°C of less than 0.5 g / L. When a surfactant is used as a dispersant for CNTs, the solvent may be heavy water. Therefore, the hydrophobic dispersant may be a dispersant having a solubility in heavy water at 25°C of less than 0.5 g / L. The hydrophobic dispersant is preferably one or more of a fluorene-based polymer, a thiophene-based polymer, and a carbazole-based polymer.

[0016] Specific examples of hydrophobic dispersants include Poly(9,9-di-n-octylfluorenyl-2,7-diyl) (PFO), Poly(9,9-di-n-dodecylfluorenyl-2,7-diyl) (PFD), 9,9-dioctylfluorene-alt-benzothiadiazole alternating polymer (Poly(9,9-dioctylfluorene-alt-benzothiadiazole)) (F8BT), Poly[(9,9-dioctylfluorene-alt-benzothiadiazole) (F8BT), Poly[(9,9-dihexylfluorenyl-2,7-diyl)-alt-(2,6-pyridine)](PFOPy), Poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(6,6'-{2,2'-bipyridine})](PFO-BPy), Poly[(9,9-dihexylfluorenyl-2,7-diyl)-co-(9,10-anthracene)](PFH-A), Regioregular poly(3-dodecylthiophene)(rr-P3DDT), and Poly(N-decyl-2,7-carbazole).

[0017] Among water-insoluble polymers that can identify the tube structure of semiconducting CNTs, such as fluorene-based polymers, thiophene-based polymers, or carbazole-based polymers, Poly(9,9-di-n-dodecylfluorenyl-2,7-diyl) (PFD), a fluorene homopolymer with dodecyl alkyl side chains, is used to select semiconducting CNTs with various tube structure indices (n, m) from a mixture of semiconducting CNTs and metallic CNTs, and disperse them in a dispersion medium such as xylene or toluene.

[0018] CNTs other than semiconducting CNTs that were not identified by PFD aggregate in the dispersion and are easily removed by settling through centrifugation. In addition, by using a polymer such as Poly(9,9-dioctylfluorene-alt-benzothiadiazole) (F8BT) or PFD, which allows identification of tube structures, as a dispersant, it becomes easier to obtain a dispersion containing large semiconducting CNTs with tube diameters of 1.2 nm or more, which are generally difficult to disperse in isolation, through low-speed centrifugation at a centrifugal force of 20,000×g or less (g: gravitational acceleration).

[0019] The semiconducting CNT-containing layer has an absorbance of 0.01 or more and an LW Int80% is 35 meV or less and LW Int50% has one or more optical absorption peaks of 70 meV or less in the near infrared wavelength region. Int80% is 35 meV or less and LW Int50% "LW Int80% is 35 meV or less, LW Int50% is 70 meV or less, or LW Int80% is 35 meV or less and LW Int50% The following is a definition of "absorbance 0.01 or more, LW Int80% is 35 meV or less and LW Int50% "One or more optical absorption peaks having an energy of 70 meV or less" may be referred to as "a specified optical absorption peak."

[0020] The near infrared wavelength range is 900nm-2000nm. Int80% is the line width of the optical absorption spectrum at the absorbance when the minimum absorbance value in the wavelength region 900 nm to 2000 nm is taken as the baseline and the peak absorbance from this baseline is 4 / 5 of the optical absorption peak. Int50% is the line width of the optical absorption spectrum at the absorbance when the peak absorbance from the above-mentioned baseline is half the optical absorption peak.

[0021] The light absorption peak may be present in a plurality of wavelengths in the near-infrared region. Of these plurality of light absorption peaks, at least one may be a predetermined light absorption peak. However, it is preferable that all of the plurality of light absorption peaks having an absorbance of 0.01 or more are predetermined light absorption peaks. When the laminate of the embodiment is used in a modified electrode that detects a substance to be detected, such as a biomolecule, by an electrochemical method, the electrode response due to the oxidation and reduction of the substance to be detected becomes clear because the semiconductor CNT-containing layer has a predetermined light absorption peak in the near-infrared wavelength region. In addition, for a substance to be detected that is capable of π-π interaction or CH-π interaction, which is a type of hydrogen bond, such as a molecule having an aromatic ring, an "electrode response according to the tube structure" that is difficult to find due to the presence of aggregates is likely to occur. Therefore, an improvement in electrode response due to the tube structure of the semiconductor CNT can be expected.

[0022] The modified electrode of the embodiment of the present application is a modified electrode for detecting a substance to be detected by an electrochemical method, and includes the laminate of the embodiment. This modified electrode is used as a working electrode of a sensor for biomolecules and the like. This sensor can be constructed, for example, by a working electrode, a reference electrode, a counter electrode (opposite electrode), a potentiostat for controlling the electrode potential between the working electrode and the reference electrode, an ammeter incorporated in the potentiostat for measuring the current flowing between the working electrode and the counter electrode, and an electrochemical measurement system including an electrolyte. This sensor using the current measurement method detects the substance to be detected by the change in the position of the potential and the current value associated with an oxidation-reduction reaction when a potential sweep is performed using an electrolyte solution containing a substance to be detected such as a biomolecule and only the electrolyte solution as a measurement solution. It is also possible to construct a sensor for biomolecules and the like in an electrochemical measurement system using a potential difference measurement method, using the modified electrode as a working electrode.

[0023] The manufacturing method of the laminate according to the embodiment of the present application includes a centrifugation step and a coating step. In the centrifugation step, the dispersion is centrifuged at a centrifugal force of 7,000×g-20,000×g for 1 hour or more to obtain a supernatant. Hereinafter, the centrifugation step at a centrifugal force of 7,000×g-20,000×g for 1 hour or more may be referred to as a "predetermined centrifugation step". The centrifugal force is preferably 15,000×g-20,000×g. The centrifugation time is preferably 1 hour or more, more preferably 2 hours or more.

[0024] The dispersion liquid contains semiconducting CNTs, a hydrophobic dispersant capable of identifying the tube structure of the semiconducting CNTs, and a dispersion medium. This hydrophobic dispersant disperses the semiconducting CNTs in the dispersion medium, but hardly disperses the metallic CNTs in an isolated state. The dispersion medium is preferably a hydrophobic dispersion medium so that the hydrophobic dispersant dissolves or is highly dispersed. Examples of hydrophobic dispersion media include p-xylene, o-xylene, m-xylene, xylene (mixture), toluene, benzene, mesitylene, ethylbenzene, and styrene.

[0025] In the coating process, the supernatant is placed on the conductive substrate, and the dispersion medium is evaporated from the supernatant to form a semiconductor CNT-containing layer on the conductive substrate. The supernatant is placed on the conductive substrate by a method such as drop casting, ultrasonic spraying, or spin coating. The supernatant contains semiconductor CNTs and a hydrophobic dispersant, but contains almost no metallic CNTs. Therefore, the semiconductor CNT-containing layer contains semiconductor CNTs and a hydrophobic dispersant. During the evaporation of the dispersion medium, the hydrophobic dispersant suppresses the aggregation of the semiconductor CNTs. Therefore, the semiconductor CNTs in the semiconductor CNT-containing layer are present in a relatively dispersed state.

[0026] In the coating step, it is preferable to form the semiconductor CNT-containing layer by evaporating the dispersion medium inside the spiral airflow while applying a spiral airflow (hereinafter, "spiral airflow" may be referred to as "spiral airflow") toward the surface of the conductive substrate. This is because the semiconductor CNTs in the semiconductor CNT-containing layer can be more dispersed. To evaporate the dispersion medium inside the spiral airflow, for example, a linear airflow in a direction away from the dispersion medium on the conductive substrate may be generated inside the spiral airflow.

[0027] Fig. 21(a) shows a schematic cross section of an apparatus 10 for forming a semiconductor CNT-containing layer using a spiral airflow. The apparatus 10 produces a semiconductor CNT-containing layer from a supernatant liquid D. The apparatus 10 includes a housing H, a base 12, a suction member 14, an airflow adjustment member 16, and an airflow cover 18. Two vents Ha for taking in gas from the outside are provided on the sides of the housing H. Also, one vent (not shown) is provided on the rear of the housing H in Fig. 21(a).

[0028] A conductive substrate (not shown) and a supernatant liquid D are placed on the base 12. A container C containing the conductive substrate and the supernatant liquid D may be placed on the base 12, or the conductive substrate and the supernatant liquid D may be placed thereon as is. The suction member 14 is provided to face the base 12. The suction member 14 evaporates the dispersion medium of the supernatant liquid D. The suction member 14 includes a cylindrical suction port 14a and a pump (not shown) connected to the suction port 14a. When the pump is operated, the dispersion medium of the supernatant liquid D placed on the base 12 evaporates and turns into vapor, and the vapor is sucked into the suction port 14a and discharged to the outside of the housing H.

[0029] The airflow adjustment member 16 is attached to the suction port 14a. The airflow adjustment member 16 generates a spiral airflow SF toward the base 12 and a linear airflow LF that moves away from the base 12 inside the spiral airflow SF (hereinafter, the "linear airflow" may be referred to as the "linear airflow") by the operation of the suction member 14. The mechanism by which the airflow adjustment member 16 generates the spiral airflow SF and the linear airflow LF will be described later.

[0030] FIG. 1(b) is a schematic diagram of a side surface of the airflow adjustment member 16. FIG. 1(c) is a schematic diagram of a cross section of the airflow adjustment member 16. The airflow adjustment member 16 includes a cylindrical first base portion 16a, a cylindrical second base portion 16b, an airflow forming portion 16c, and a spring 16d. The first base portion 16a and the second base portion 16b are integrated so that there is a slight difference in their inner diameters and a step is formed. The outer diameter of the first base portion 16a is slightly larger than the outer diameter of the second base portion 16b.

[0031] The airflow forming part 16c is attached to the outside of the second base part 16b. The airflow forming part 16c can move toward the lower end of the first base part 16a along the outer wall of the second base part 16b, which serves as a support (guide). The airflow forming part 16c has a truncated cone shape with a cylindrical hollow part formed in the center. The outer diameter of the lower end of the second base part 16b is larger than the inner diameter of the airflow forming part 16c so that the airflow forming part 16c does not detach from the second base part 16b. A spiral groove (hereinafter sometimes referred to as a "spiral groove") 16cg is formed on the outer periphery of the airflow forming part 16c.

[0032] The spring 16d is provided around the second base 16b between the lower end of the first base 16a and the upper end of the airflow forming part 16c. The length from the lower end of the first base 16a to the upper end of the airflow forming part 16c can be adjusted while receiving a repulsive force from the spring 16d. For example, when removing a dispersion medium from a dispersion liquid, the spring 16d presses the mouth of a container containing the dispersion liquid and the airflow forming part 16c to bring the two into close contact.

[0033] The airflow cover 18 is provided on the upper surface of the base 12 so as to surround the supernatant liquid D. The airflow cover 18 is a member for efficiently applying a spiral airflow SF to the surface of the supernatant liquid D. The airflow cover 18 includes a wall portion 18a and a cylindrical portion 18b. The wall portion 18a has a hollow truncated cone shape, is open at the top and bottom, and has a smaller inner diameter toward the suction member 14. The cylindrical portion 18b is connected to an opening 18as of the wall portion 18a having a smaller inner diameter. In this embodiment, the wall portion 18a and the cylindrical portion 18b are integral. The periphery of the upper end of the airflow forming portion 16c is in contact with the inner wall of the cylindrical portion 18b, except for the opening at the upper end of the spiral groove 16cg. That is, the uppermost end 18c of the airflow cover 18 is disposed above the spiral groove 16cg.

[0034] Therefore, the air taken into the airflow cover 18 passes through the spiral groove 16cg from the opening at the upper end of the spiral groove 16cg, and the spiral airflow SF is efficiently applied to the surface of the supernatant liquid D. The periphery of the airflow forming part 16c other than the upper end may be in contact with the inner wall of the uppermost end 18c of the airflow cover 18. Even if the inner wall of the uppermost end 18c of the airflow cover 18 is in contact with the periphery of the airflow forming part 16c other than the upper end, the air that has passed through the spiral groove 16cg from the middle of the spiral groove 16cg is taken into the airflow cover 18. In this case, it is preferable that the air taken into the airflow cover 18 be in contact with the inner wall of the uppermost end 18c of the airflow cover 18 at a position higher than 2 / 3 of the height of the airflow forming part 16c so that the air taken in can pass through the spiral groove 16cg for a long distance. The airflow cover 18 may be composed of only the hollow truncated cone-shaped wall part 18a.

[0035] When the pump operates, air inside the housing H is sucked in through the suction port 14a. That is, a linear airflow LF is generated from the base 12 toward the suction port 14a. At the same time, in order to eliminate the pressure difference between the inside and outside of the housing H, air is taken in from the outside of the housing H into the inside of the housing H through the ventilation port Ha. This taken-in air passes through the spiral groove 16cg, enters the inside of the airflow cover 18, and flows toward the base 12. At this time, since the air moves along the spiral groove 16cg and the diffusion of the air is restricted by the airflow cover 18, a spiral airflow SF is generated from the airflow adjustment member 16 toward the base 12.

[0036] The spiral airflow SF stirs the supernatant liquid D in a circular shape, and the centrifugal force generated in the supernatant liquid D makes it difficult for the semiconductor CNTs to aggregate toward the center. Inside the spiral airflow SF, that is, near the center of the supernatant liquid D, the dispersion medium is evaporated by the straight airflow LF, so the semiconductor CNTs are also drawn toward the center. The balance between the centrifugal force acting on the semiconductor CNTs and the force toward the center makes it possible to dry the semiconductor CNTs while suppressing aggregation, and a semiconductor CNT-containing layer in which the semiconductor CNTs are dispersed is obtained. EXAMPLES

[0037] Example 1 Approximately 20 mg of PFD (Sigma-Aldrich, molecular weight 8,195 (same below)) and approximately 5 mg of SWCNT powder (Raymor Industries Inc., PlasmaTube Single-Wall Carbon Nanotube (RN-220), tube diameter 0.9 nm-1.5 nm (same for comparative examples)) synthesized by the plasma torch method were mixed in an organic dispersion medium, p-xylene, and the mixture of Example 1 was prepared by ultrasonic dispersion treatment.

[0038] In this ultrasonic dispersion treatment, ultrasonic irradiation was performed for about 10 hours using a bath-type ultrasonic cleaner (ULTRASONIC CLEANER, USK-1R, 40 kHz, 55 W, manufactured by As-one) and ultrasonic irradiation for 10 minutes using a tip-type ultrasonic mixer / crusher (ultrasonic homogenizer, Q700, 20 kHz, 700 W, manufactured by QSONICA). The mixture of Example 1 was centrifuged for 2 hours at a centrifugal force of 15,000×g (ultracentrifuge, CS120FNX, manufactured by Hitachi Koki Co., Ltd.) to obtain a supernatant. Approximately 80% of this supernatant was collected to obtain the semiconductor SWCNT dispersion of Example 1 for surface modification of a carbon substrate.

[0039] A spectrophotometer (HITACHI, U-4100 (same below)) was used to obtain the optical absorption spectra of the mixture of Example 1 and the semiconducting SWCNT dispersion. The optical absorption of the dispersion medium was corrected by a baseline measurement using the organic dispersion medium p-xylene (same below). Figure 1 shows the optical absorption spectra of the mixture of Example 1 ("CNT dispersion before centrifugation treatment" in the figure, solid line) and the semiconducting SWCNT dispersion of Example 1 ("raw material of Example 1" in the figure, circle). As shown in Figure 1, optical absorption peaks (M1) of metallic SWCNTs were observed in the mixture at wavelengths of around 645 nm and 690 nm.

[0040] On the other hand, in the semiconducting SWCNT dispersion, no optical absorption peak of metallic SWCNTs was observed, and in addition to a clear optical absorption peak (S2) in the wavelength region of 700-1100 nm, a sharp optical absorption peak (S1) was observed in the near infrared region with wavelengths of 1200 nm or more. Note that M1 in Figure 1 indicates the optical transition occurring between the first singular points (between the first band) of metallic SWCNTs, and S1, S2, and S3 indicate the optical transitions occurring between the first singular points, second singular points, and third singular points, respectively, of semiconducting SWCNTs.

[0041] A near-infrared photoluminescence measurement device (Shimadzu, NIR-PL system (hereinafter the same)) was used to measure the two-dimensional photoluminescence (PL) spectrum of the semiconducting SWCNT dispersion of Example 1. The excitation wavelength and detection wavelength were scanned at intervals of 5 nm and 2 nm, respectively. Figure 2 is a two-dimensional PL map of the semiconducting SWCNT dispersion of Example 1. The vertical axis of Figure 2 is the excitation wavelength, and the horizontal axis is the emission wavelength (detection wavelength).

[0042] Luminescence was observed from semiconducting SWCNTs with various tube structure indices (n, m). In particular, the semiconducting SWCNT with tube structure indices (11, 9) has an optical absorption peak S1 at a wavelength of about 1640 nm in the optical absorption spectrum shown in Figure 1. As shown in Figure 2, the tube diameter of this semiconducting SWCNT with tube structure indices (11, 9) is 1.377 nm. Here, the tube diameter d t was calculated from the following formula using the tube structure index (n, m) (hereinafter the same). c-c was set to 0.144 nm.

[0043]

number

[0044] Analysis of the optical absorption spectrum (Fig. 1) and two-dimensional PL map (Fig. 2) revealed that the semiconducting SWCNT dispersion of Example 1 contained semiconducting SWCNTs with tube diameters of 1.03 nm to 1.52 nm. By coating such a semiconducting SWCNT dispersion having a sharp optical absorption peak on a substrate such as a quartz substrate or a carbon substrate, a laminate comprising the substrate and semiconducting SWCNTs dispersed independently on the substrate can be easily obtained.

[0045] Using 279 μL of the semiconductor SWCNT dispersion of Example 1, the semiconductor SWCNT composites of Example 1A (drop casting method) and Example 1B (spiral airflow method), which are laminates including a quartz substrate and a semiconductor SWCNT-containing layer on the quartz substrate, were fabricated by two methods, the drop casting method and the "spiral airflow method" described below. The quartz substrate was a quartz substrate for spectroscopic measurement, and had a surface roughness R a is about 1.5 nm, not more than 2.0 nm (the same applies below). The spiral airflow method of Example 1B is a method for forming a semiconducting SWCNT-containing layer on a quartz substrate by applying a spiral airflow toward the surface of a semiconductor SWCNT dispersion on a quartz substrate and evaporating the dispersion medium inside the spiral airflow.

[0046] More specifically, a quartz substrate with the surface coated with the semiconductor SWCNT dispersion was placed in a 125 mL Erlenmeyer flask, and an evaporator utilizing a spiral airflow (Biochromate Co., Ltd., Convenience Evapo C1, Flow Meter CEFM, Spiral Plug SP-P4 (hereinafter the same)) was used to dry the semiconductor SWCNT dispersion of Example 1 for approximately 8.5 hours while applying a spiral airflow at a flow rate of 15 L / min to the surface of the quartz substrate, thereby obtaining the semiconductor SWCNT composite of Example 1B. The spiral airflow method can further suppress the aggregation of the semiconductor SWCNTs during the formation of the semiconductor SWCNT-containing layer.

[0047] The optical absorption spectra of the semiconductor SWCNT composites of Examples 1A and 1B were measured using a spectrophotometer. The optical absorption of the quartz substrate was corrected by a baseline measurement using the same quartz substrate for spectroscopic measurement (same below). Figures 3 and 4 show the optical absorption spectra of the semiconductor SWCNT composites of Examples 1A and 1B, respectively. The horizontal axis at the bottom of Figures 3 and 4 represents photon energy. As shown in Figure 3, the semiconductor SWCNT composite of Example 1A obtained by the drop casting method exhibited an LW of approximately 33 meV at a wavelength of 1669 nm (photon energy 0.7428 eV). Int80% It showed a near infrared absorption peak.

[0048] As shown in FIG. 4, the semiconductor SWCNT complex of Example 1B obtained by the spiral airflow method exhibited LWs of about 22 meV and about 26 meV at wavelengths of 1590 nm (photon energy 0.7797 eV) and 1664 nm (photon energy 0.7450 eV). Int80% In other words, the spiral airflow method was used to measure the near-infrared absorption peak of LW Int80% Thus, by using the semiconductor SWCNT dispersion of Example 1, the semiconductor SWCNT complex formed on the substrate had an extremely narrow LW Int80% The semiconductor-SWCNT complex of Example 1B has one or more near-infrared absorption peaks with a narrow spectral linewidth of 35 meV or less. Note that, in the production process, no drying treatment by heating the substrate was performed on the semiconductor-SWCNT complex of Example 1B.

[0049] In order to prepare a modified electrode for electrochemical measurement, the semiconductor SWCNT dispersion of Example 1 having a steep optical absorption peak was used to prepare a carbon electrode substrate, which is a flat carbon substrate, and a semiconductor SWCNT-containing layer on the carbon electrode substrate, a semiconductor SWCNT composite of Example 1C, which is a laminate, in the following manner. By the advanced magnetron sputtering (UBM sputtering) method described in Patent Document 1 and Non-Patent Document 2, sp 2 Bonds and sp 3 A conductive carbon layer having bonds was formed to a thickness of about 40 nm.

[0050] At this time, the target material was sintered carbon, the argon gas pressure was 0.6 Pa, and the target power was 400 W. The p-type silicon wafer and the conductive carbon layer constituted a carbon electrode substrate. The surface roughness R a The thickness of the carbon electrode was about 0.3 nm, which was less than 1.0 nm. In order to evaluate the electrode characteristics using a plate electrode evaluation cell kit described later, this carbon electrode substrate was cut into a rectangle of 17 to 25 mm length x 12 to 15 mm width.

[0051] The carbon electrode substrate, in which 100 μL of the semiconducting SWCNT dispersion of Example 1 was applied to the surface of the conductive carbon layer, was placed in a 50 mL Erlenmeyer flask. Using an evaporator utilizing a spiral airflow, the semiconducting SWCNT dispersion was dried for about 20 minutes while applying a spiral airflow at a flow rate of 5 L / min to the surface of the carbon electrode substrate, to obtain a semiconducting SWCNT composite of Example 1C having a circular semiconducting SWCNT-containing layer with a diameter of about 8 mm (hereinafter, the "semiconducting SWCNT composite of Example 1C" may be referred to as the "modified electrode of Example 1"). FIG. 5 shows the top surface of the semiconducting SWCNT composite of Example 1C. The semiconducting SWCNT-containing layer functions as an electrode response portion. The semiconducting SWCNT composite of Example 1C has a semiconducting SWCNT-containing layer containing semiconducting SWCNTs with a tube diameter of 1.03 nm-1.52 nm.

[0052] Using an electrochemical analyzer (BAS potentiostat, ALS1240B) and a plate electrode evaluation cell kit (BAS electrode cell kit, reaction volume approximately 1 mL, inner electrode diameter of liquid contact portion approximately 7.8 mm), cyclic voltammetry (CV), an electrochemical technique, was performed at a potential sweep rate of 0.1 V / s using a three-electrode method in which the semiconducting SWCNT composite of Example 1C was used as the working electrode, an Ag / AgCl electrode as the reference electrode, and a Pt wire as the counter electrode. As a calibration substance for evaluating the electrode characteristics, hexaamine ruthenium (III) chloride (Ru(NH3)6, a reversible redox species, was used. 2+ / 3+ ) or potassium ferricyanide (Fe(CN)6 3- / 4- ), or 3-hydroxy-DL-kynurenine (3HK), a type of biomolecule that has an aromatic ring.

[0053] Figure 6 shows the Ru(NH3)6 2+ / 3+ CV curve of Ru(NH3)6 at 1mM. 2+ / 3+ The measurement sample was a 1M KCl solution containing Ru(NH3)6 2+ / 3+ is generally known as a material that is not sensitive to the surface state of the electrode. As shown in Figure 6, a clear oxidation peak (E pa) and a clear reduction peak at potential -0.223 V (E pc The peak potential difference between oxidation and reduction (ΔE p ) was 89mV.

[0054] Figure 7 shows the structure of Fe(CN)6 3- / 4- CV curve of Fe(CN)6 at 1mM. 3- / 4- The measurement sample was a 1M KCl solution containing Fe(CN)6 3- / 4- is generally known to be a material that is sensitive to the surface state of the electrode. As shown in Figure 7, it showed a clear oxidation peak at a potential of 0.309 V and a clear reduction peak at a potential of 0.204 V. The peak potential difference between the oxidation and reduction was 105 mV.

[0055] Figure 8 shows the CV curve of 3HK. The measurement sample was a 50 mM phosphate buffer (pH 7.0) containing 1 mM 3HK. 3HK is an aromatic amino acid that is a metabolite of tryptophan. As shown in Figure 8, a clear oxidation peak was observed at a potential of 0.632 V.

[0056] Comparison example (short centrifugation with weak centrifugal force) The mixture of Example 1 was centrifuged for 5 minutes at a centrifugal force of 5,000×g (Sigma micro mini centrifuge, 1-14PP) to obtain a supernatant. Approximately 80% of this supernatant was collected to obtain a comparative SWCNT dispersion for surface modification of a carbon substrate. Since the centrifugation was performed at a weaker centrifugal force and for a shorter time than in Example 1, the SWCNT dispersion of the comparative example contains not only semiconducting SWCNTs but also significantly more metallic SWCNTs than the semiconducting SWCNT dispersion of Example 1.

[0057] A spectrophotometer was used to obtain the optical absorption spectrum of the SWCNT dispersion of the comparative example. FIG. 9 shows the optical absorption spectrum of the SWCNT dispersion of the comparative example (in the figure, "Raw material (CNT dispersion) of the comparative example," solid line). FIG. 9 also shows the optical absorption spectrum of the semiconductor SWCNT dispersion of Example 1 (in the figure, "Raw material (semiconductor CNT dispersion) of Example 1," dotted line). As shown in FIG. 9, in the SWCNT dispersion of the comparative example, optical absorption peaks (M1) of metallic SWCNTs were observed at wavelengths of about 645 nm and about 690 nm. In addition, the SWCNT dispersion of the comparative example, in which aggregates and the like were mixed, showed optical absorption peaks (S1, S2) that were much broader than those of the semiconductor SWCNT dispersion of Example 1.

[0058] Using 279 μL of the SWCNT dispersion of the comparative example, a SWCNT-containing layer was formed on a quartz substrate by the drop casting method, and a comparative SWCNT composite was produced as a laminate comprising this quartz substrate and the SWCNT-containing layer on the quartz substrate. Figure 10 shows the optical absorption spectrum of this SWCNT composite (in the figure, "semiconductor CNT composite (drop casting method)"). The horizontal axis at the bottom of Figure 10 represents photon energy. As shown in Figure 10, the optical absorption spectrum of the comparative SWCNT composite exhibited a broad spectral shape.

[0059] In addition, for the near-infrared absorption peak at a wavelength of 1666 nm (photon energy 0.7441 eV), the spectral linewidth (LW) estimated at 85% of the peak absorbance from the baseline was Int85% ) was about 37 meV, exceeding 35 meV. Int80% As compared with the semiconducting SWCNT composites of Examples 1A and 1B, which have a spectral linewidth of 35 meV or less, the near-infrared light absorption peak was much broader.

[0060] A comparative modified electrode having a comparative SWCNT-containing layer with a circular shape having a diameter of about 10 mm was obtained on the same conductive carbon layer as in Example 1C by a drop casting method using 175 μL of the comparative SWCNT dispersion and air drying for about 20 hours. CV measurement was performed using the comparative modified electrode as the working electrode under the same measurement conditions as in Example 1 using the same device and the same calibration substance as in Example 1.

[0061] FIG. 11 shows the Ru(NH3)6 concentration measured using the comparative modified electrode as the working electrode. 2+ / 3+ The CV curve (solid line) of Ru(NH3)6 was measured using the modified electrode of Example 1 as the working electrode. 2+ / 3+ The CV curve of the modified electrode of the comparative example (in the figure, "modified electrode of the present invention", dotted line) is also shown. The CV curve of the modified electrode of the comparative example showed an oxidation peak at a potential of about -0.127 V and a reduction peak at a potential of about -0.235 V. The peak potential difference between the oxidation and reduction was 108 mV.

[0062] FIG. 12 shows the Fe(CN)6 3- / 4- The CV curve (solid line) of Fe(CN)6 was measured using the modified electrode of Example 1 as the working electrode. 3- / 4- 12, the CV curve of the modified electrode of the comparative example was much broader than that of the modified electrode of Example 1, as in FIG. 11. The CV curve of the modified electrode of the comparative example showed an oxidation peak at a potential of about 0.419 V and a reduction peak at a potential of about 0.005 V. The peak potential difference between oxidation and reduction in the CV curve of the modified electrode of the comparative example, 414 mV, was about four times the peak potential difference between oxidation and reduction in the CV curve of the modified electrode of the comparative example, 105 mV (see FIG. 7).

[0063] Fig. 13 shows a CV curve (solid line) of 3HK measured using the modified electrode of the comparative example as the working electrode. Fig. 13 also shows a CV curve of 3HK measured using the modified electrode of Example 1 as the working electrode ("modified electrode of the present invention" in the figure, dotted line) and a CV curve of phosphate buffer (concentration 50 mM, pH 7.0) measured using the modified electrode of the comparative example as the working electrode ("background (phosphate buffer)" in the figure, dashed line). Unlike the CV curve using the modified electrode of Example 1, in the CV curve using the modified electrode of the comparative example, no oxidation peak was observed even when the potential was swept up to 0.7 V, but an oxidation peak was observed around a potential of 0.84 V when the potential was swept up to 0.9 V.

[0064] As can be seen from the background CV curve measured using the comparative modified electrode as the working electrode in Fig. 13, a slight increase in background current occurs when sweeping toward the high potential side. Therefore, in the CV curve of 3HK measured using the comparative modified electrode as the working electrode, the oxidation peak tends to become unclear due to the influence of the background current on the high potential side of 0.7 V or more.

[0065] The modified electrodes of Comparative Example and Example 1 were prepared from the same mixed solution containing the same SWCNT powder synthesized by the plasma torch method and the same dispersant (PFD). However, the centrifugal separation process used to prepare the SWCNT dispersion from the mixed solution was different between Comparative Example and Example 1. For this reason, as shown in Figures 11 to 13, the CV curve using the modified electrode of Comparative Example was much broader than the CV curve using the modified electrode of Example 1. In other words, it was found that the modified electrode of Example 1 had superior electrode response to various types of target substances compared to the modified electrode of Comparative Example.

[0066] Example 2 A semiconducting SWCNT dispersion of Example 2 was obtained in the same manner as in Example 1, except that SWCNT powder (NanoIntegris Inc., HiPco (Raw Powder), Batch #HR31-96A, tube diameter 0.8 nm-1.2 nm) synthesized by the HiPco method (High-pressure carbon monoxide method) instead of the plasma torch method was used, and the centrifugation time of the mixture was changed to 1 hour.

[0067] The optical absorption spectrum of the semiconducting SWCNT dispersion of Example 2 was obtained in the same manner as in Example 1. Fig. 14 shows the optical absorption spectrum of this semiconducting SWCNT dispersion (in the figure, "Raw material of Example 2 (semiconducting SWCNT dispersion)", circles). Fig. 14 also shows the optical absorption spectrum of the semiconducting SWCNT dispersion of Example 1 (in the figure, "Raw material of Example 1 (semiconducting SWCNT dispersion)", solid line).

[0068] As shown in FIG. 14, the semiconductor SWCNT dispersion of Example 2, which contains semiconductor SWCNTs with a smaller tube diameter than that of the semiconductor SWCNT dispersion of Example 1, had a clear light absorption peak (S2) in the wavelength region of 550-850 nm and a sharp light absorption peak (S1) in the near-infrared region of wavelengths of 950 nm or more, similar to the semiconductor SWCNT dispersion of Example 1. However, the light absorption peaks (S1, S2) of the semiconductor SWCNT dispersion of Example 2 appear on the slightly shorter wavelength side compared to the light absorption peaks (S1, S2) of the semiconductor SWCNT dispersion of Example 1, because the tube diameter of the semiconductor SWCNTs contained in the dispersion is small. The maximum absorbance of the near-infrared light absorption peak of the semiconductor SWCNT dispersion of Example 2 (about 0.279) was similar to the maximum absorbance of the near-infrared light absorption peak of the semiconductor SWCNT dispersion of Example 1 (about 0.260).

[0069] The two-dimensional PL spectrum of the semiconducting SWCNT dispersion of Example 2 was measured in the same manner as in Example 1, except that the detection wavelength was scanned at 1 nm intervals. Figure 15 is a two-dimensional PL map of the semiconducting SWCNT dispersion of Example 2. As shown in Figure 15, among the semiconducting SWCNTs contained in the semiconducting SWCNT dispersion of Example 2, various semiconducting SWCNTs with tube structure indices (6,5), (7,5), (7,6), (8,6), (8,7), (9,5), and (10,3) emitted prominently.

[0070] In addition, from the analysis of the optical absorption spectrum (FIG. 14) and the two-dimensional PL map (FIG. 15), it was found that the semiconducting SWCNT dispersion of Example 2 contained, in addition to the above-mentioned semiconducting SWCNTs that emitted remarkably, semiconducting SWCNTs with a tube structure index of (9,8) that emitted weak light at a wavelength of about 1435 nm when excited with light at a wavelength of 815 nm, and contained semiconducting SWCNTs with a tube diameter of 0.757 nm-1.17 nm. In particular, the semiconducting SWCNTs with a tube structure index of (7,6) have an optical absorption peak of S1 at a wavelength of about 1130 nm, as shown in FIG. 14. The tube diameter of this semiconducting SWCNT with a tube structure index of (7,6) is 0.895 nm, as shown in FIG. 15.

[0071] In the same manner as in Example 1A and Example 1B, the semiconductor SWCNT composites of Example 2A (drop casting method) and Example 2B (spiral airflow method), which are laminates including a quartz substrate and a semiconductor SWCNT-containing layer on the quartz substrate, were produced by two methods, the drop casting method and the spiral airflow method, using 279 μL of the semiconductor SWCNT dispersion of Example 2. The optical absorption spectra of the semiconductor SWCNT composites of Example 2A and Example 2B were measured using a spectrophotometer.

[0072] 16 and 17 show the optical absorption spectra of the semiconductor-SWCNT complexes of Examples 2A and 2B, respectively. The horizontal axis at the bottom of each of Figs. 16 and 17 represents photon energy. As shown in Fig. 16, the semiconductor-SWCNT complex of Example 2A obtained by the drop casting method exhibits an LW of about 62 meV at a wavelength of 1144 nm (photon energy 1.0837 eV). Int50% (full width at half maximum) near-infrared light absorption peak.

[0073] As shown in FIG. 17, the semiconductor SWCNT complex of Example 2B obtained by the spiral airflow method had LW at a wavelength of 1137 nm (photon energy 1.0904 eV), a wavelength of 1281 nm (photon energy 0.9678 eV), and a wavelength of 990 nm (photon energy 1.2523 eV). Int50% In this way, even though the synthesis method of the SWCNTs contained in the semiconductor SWCNT dispersion was different from that of the SWCNTs contained in the semiconductor SWCNT dispersion of Example 1, the semiconductor SWCNT complexes of Example 2A and Example 2B exhibited near-infrared absorption peaks of about 34 meV, about 41 meV, and about 49 meV, respectively, as shown in Figs. 16 and 17. Int50% It has one or more narrow near-infrared absorption peaks of 70 meV or less.

[0074] Furthermore, except for changing the flow rate of the spiral airflow to 10 L / min, a semiconductor SWCNT composite of Example 2C (hereinafter, the "semiconductor SWCNT composite of Example 2C" may be referred to as the "modified electrode of Example 2"), which is a laminate including a conductive carbon layer and a semiconductor SWCNT-containing layer on this conductive carbon layer, was obtained using the semiconductor SWCNT dispersion of Example 2 in the same manner as in Example 1. Then, using the same device and the same calibration substance as in Example 1, CV measurement was performed with the modified electrode of Example 2 as the working electrode under the same measurement conditions as in Example 1.

[0075] FIG. 18 shows the Ru(NH3)6 concentration measured using the modified electrode of Example 2 as the working electrode. 2+ / 3+ The CV curve (solid line) of Ru(NH3)6 was measured using the modified electrode of Example 1 as the working electrode. 2+ / 3+The CV curve (dotted line) of Example 2 is also shown. The CV curve using the modified electrode of Example 2 is similar to that using the modified electrode of Example 1, and shows an oxidation peak at a potential of about -0.131 V and a reduction peak at a potential of about -0.224 V. The peak potential difference between oxidation and reduction was 93 mV, which was a narrow potential width comparable to the peak potential difference between oxidation and reduction of the CV curve using the modified electrode of Example 1, 89 mV (see FIG. 6).

[0076] FIG. 19 shows the relationship between the concentration of Fe(CN)6 and the modified electrode of Example 2. 3- / 4- The CV curve (solid line) of Fe(CN)6 was measured using the modified electrode of Example 1 as the working electrode. 3- / 4- 19 also shows a CV curve (dotted line) of 100 mV. As shown in Fig. 19, the CV curve using the modified electrode of Example 2 is similar to that using the modified electrode of Example 1, and shows an oxidation peak at a potential of about 0.311 V and a reduction peak at a potential of about 0.204 V. The peak potential difference between oxidation and reduction was 107 mV, which was a narrow potential width comparable to the peak potential difference between oxidation and reduction of the CV curve using the modified electrode of Example 1, 105 mV (see Fig. 7).

[0077] Fig. 20 shows a CV curve (solid line) of 3HK measured using the modified electrode of Example 2 as the working electrode. Fig. 20 also shows a CV curve (dotted line) of 3HK measured using the modified electrode of Example 1 as the working electrode. As shown in Fig. 20, the CV curve using the modified electrode of Example 2 showed an oxidation peak at a potential of about 0.468 V. Compared with the oxidation peak potential of 0.632 V (see Fig. 8) of the CV curve using the modified electrode of Example 1, the oxidation peak potential of the CV curve using the modified electrode of Example 2 shifted to the lower potential side by 0.164 V.

[0078] Calibrator Ru(NH3)6 used to evaluate electrode properties 2+ / 3+ and Fe(CN)6 3- / 4-Unlike the CV curve of Example 1, the oxidation peak potential in the CV curve of 3HK, which has an aromatic ring in the molecular skeleton, was significantly shifted to the lower potential side due to the difference in the tube structure of the semiconducting SWCNT contained in the modified electrode of Example 1 and Example 2. This peak potential shift was due to the difference in the tube structure index (11,9) of the semiconducting SWCNT (d t : 1,377 nm) and the semiconducting SWCNT with a tube structure index of (7,6) contained in the modified electrode of Example 2 (d t The potential difference was close to the potential difference (approximately 0.175 V) of the modified electrode estimated from the respective electron potentials of the electrodes (100 nm: 0.895 nm).

[0079] When estimating the electrode potential difference due to the electronic potential of the semiconducting SWCNT, reference can be made to, for example, Non-Patent Document 3, which evaluates the electronic potential using a PL spectroelectrochemical technique. In addition, as shown in FIG. 20, the tube diameter d t The CV curve using the modified electrode of Example 2 containing semiconducting SWCNTs with a decreased tube curvature (increased tube curvature) showed a higher oxidation peak current (I pa ) significantly decreased. [Explanation of symbols]

[0080] 10 equipment 12 Foundation 14 Suction member 14a Suction port 16 Air flow adjustment member 16a First base 16b Second base 16c Airflow forming section 16cg spiral groove 16d Spring 18 Airflow Cover 18a Wall section 18as Small inner diameter opening 18b Cylindrical section H-frame Ha Vent D. Supernatant C container SF Spiral Airflow LF Straight Airflow

Claims

1. A conductive substrate; a semiconducting carbon nanotube-containing layer provided on the conductive substrate, the semiconducting carbon nanotube-containing layer including a hydrophobic dispersant capable of identifying the tube structure of the semiconducting carbon nanotube; having The semiconductor carbon nanotube-containing layer has an absorbance of 0.01 or more and an LW Int80% is 35 meV or less and LW Int50% A laminate having one or more optical absorption peaks of 70 meV or less in the near infrared wavelength region.

2. In claim 1, The surface roughness R of the conductive substrate a The laminate has a thickness of 1.0 nm or less.

3. In claim 2, The laminate, wherein the conductive substrate is a carbon substrate.

4. A modified electrode for detecting a target substance by an electrochemical method, comprising: A modified electrode comprising the laminate of any one of claims 1 to 3.

5. a centrifugation step of centrifuging a dispersion containing semiconducting carbon nanotubes, a hydrophobic dispersant capable of identifying the tube structure of the semiconducting carbon nanotubes, and a dispersion medium at a centrifugal force of 7,000×g to 20,000×g for 1 hour or more to obtain a supernatant; a coating step of placing the supernatant on a conductive substrate and evaporating the dispersion medium to form a semiconducting carbon nanotube-containing layer on the conductive substrate, the semiconducting carbon nanotubes and the hydrophobic dispersant being included therein; A method for producing a laminate having the above structure.

6. In claim 5, A method for manufacturing a laminate in which, in the coating step, a spiral air flow is applied toward the surface of the conductive substrate while evaporating the dispersion medium inside the spiral air flow to form a semiconducting carbon nanotube-containing layer.

Citation Information

Patent Citations

  • Electrodes and Electrochemical Measurement Systems

    JP6752432B1